Pengelompokan Jenis Penerimaan Pajak di Kota Makassar Menggunakan Fuzzy Clustering - Irwan Irwan; Sahlan Sidjara; Asmelia Putri Aryati (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This research discusses grouping types of tax receipts in the City of Makassar with the method of Fuzzy C-Means (FCM). The data used are secondary data from the tax office in the form of the amount of the receipts of income tax, value-added tax, and land tax building each district in the year 2018. The discussion starts from the theory of fuzzy clustering, simulation, and the characteristics of the simulation results. In this study, the obtained number of clusters the optimum, namely the 7 clusters that have the potential for tax revenue is relatively high, namely at cluster seven consists only of the District Tamalanrea, and the lowest in the cluster a sixth consisting of the Kecamatan Tallo, Ujung Tanah, and Sangkarrang. After hashing on a cluster that is formed can be used to see the level of the welfare of the community in each district.